2018
DOI: 10.1177/1947603518796125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micronized Cartilage Matrix on Cartilage Repair in Osteochondral Lesions of the Talus

Abstract: Background The repair of osteochondral lesions remains a challenge due to its poor vascularity and limited healing potential. Micronized cartilage matrix (MCM) is dehydrated, decellularized, micronized allogeneic cartilage matrix that contains the components of native articular tissue and is hypothesized to serve as a scaffold for the formation of hyaline-like tissue. Our objective was to demonstrate in vitro that the use of MCM combined with mesenchymal stem cells (MSCs) can lead to the formation of hyaline-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Currently, no human trials have been conducted to demonstrate the efficacy of micronized allogenic cartilage matrix grafting; however, studies using equine and porcine models have demonstrated the generation of hyaline-like cartilage in cartilaginous lesions after the use of micronized allogenic cartilage matrix 11,12 . Use of micronized cartilage matrix with the combination of cells described as mesenchymal stem cells has also been demonstrated to generate hyaline-like cartilage in vitro 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no human trials have been conducted to demonstrate the efficacy of micronized allogenic cartilage matrix grafting; however, studies using equine and porcine models have demonstrated the generation of hyaline-like cartilage in cartilaginous lesions after the use of micronized allogenic cartilage matrix 11,12 . Use of micronized cartilage matrix with the combination of cells described as mesenchymal stem cells has also been demonstrated to generate hyaline-like cartilage in vitro 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies published as recently as 2018 have demonstrated hyaline chondrogenesis and differentiation of chondrocytes using MCM after just 3 weeks when combined with mesenchymal stem cells. 28 Furthermore, some studies investigating the efficacy of MCM in osteochondral lesions of the ankle joint have shown good short-to intermediate-term results. Ahmad and Maltenfort reported their findings on 30 consecutive patients over a three-year span, including an average increase in Foot and Ankle Ability Measure scores from 51.4 to 89.3 and a decrease in Visual Analog Scale from 8.1 to 1.7 at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Articular cartilage, as the cartilage tissue covering the joint surface, is of great significance in reducing the load-bearing pressure, increasing the stress area, and lubricating the joint [ 2 ], so as to effectively protect the articular surface and maintain the normal movement of the joint. As the most frequently used joint in daily life and work, ankle joint should not only bear the heavy pressure of the body, but also bear the daily walking and movement [ 3 ]. As a result, articular cartilage of talus is easily damaged due to trauma, joint degradation, arthritis, and other reasons, resulting in rough joint surface, joint pain, and limited activity, which will seriously affect the life quality of patients.…”
Section: Introductionmentioning
confidence: 99%